2022
DOI: 10.26434/chemrxiv-2022-g2h9s
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Iterative Synthesis of 1,3-Polyboronic Esters with High Stereocontrol: Applications to Bahamaolide A and Polyfunctionalised Hydrocarbons

Abstract: Polyketide natural products often contain common repeat motifs, e.g., propionate, acetate and deoxypropionate, and so can be synthesized by using iterative processes. We report a highly efficient iterative strategy for the synthesis of polyacetates based on boronic ester homologation that does not require functional group manipulation between iterations. This process involves sequential asymmetric diboration of a terminal alkene, forming a 1,2-bis(boronic ester), followed by regio- and stereoselective homologa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…4 The ability of sparteine to coordinate alkyl lithium reagents and generate configurationally stable anions was first developed in the 1990s and is still commonly leveraged in modern total syntheses. 5,6 Despite its broad use and ready extraction from Lupinus plants, periodic supply chain issues have motivated the development of synthetic approaches to access sparteine or sparteine surrogates. 7 Here we report a concise gram-scale synthesis of (±)-sparteine from the commodity chemicals pyridine and glutaryl chloride.To date, over 20 total syntheses of sparteine have been reported.…”
mentioning
confidence: 99%
“…4 The ability of sparteine to coordinate alkyl lithium reagents and generate configurationally stable anions was first developed in the 1990s and is still commonly leveraged in modern total syntheses. 5,6 Despite its broad use and ready extraction from Lupinus plants, periodic supply chain issues have motivated the development of synthetic approaches to access sparteine or sparteine surrogates. 7 Here we report a concise gram-scale synthesis of (±)-sparteine from the commodity chemicals pyridine and glutaryl chloride.To date, over 20 total syntheses of sparteine have been reported.…”
mentioning
confidence: 99%
“…Indeed, by use of a comprehensive knowledge base of individual reactions, iterative methods can also now be recognized by computer algorithms in the construction of complex molecules . We recently reported the iterative synthesis of 1,3-polyols through a sequence of asymmetric alkene diboration and selective homologation of the resulting primary boronic ester with a metalated butenyl TIB ester A (Figure B, M = Li, MgCl, TIB = 2,4,6-triisopropyl­benzoyl) . We reasoned that performing anti-Markovnikov hydroboration, instead of diboration, followed by homologation with the same metalated butenyl TIB ester A could provide an iterative strategy for the construction of 1,5-polyols in just two steps per iteration rather than three (Figure C).…”
mentioning
confidence: 99%
“…With fragments 4 and 5 in hand, we turned our attention to their union through a stereocontrolled lithiation–borylation reaction. , Before embarking on this key C–C bond forming reaction, we wanted to explore what level of substrate control might be imparted by the neighboring six-ring acetonide moiety in TIB ester 5 . Previously, Hoppe reported that the five-ring acetonide in carbamate 30 exerted strong control over stereoselectivity in the deprotonation with s BuLi in the absence of diamine ligands (Scheme A) .…”
mentioning
confidence: 99%